Efficiency of Technology of Access to Databases - Barczak, Andrzej; Mościcki, Artur (Studia Informatica. System and information technology, 2006)
In this paper the evolution of technologis of access to databases is presented. For definite sysytems of databases’ management (databases servers) and technologis of access, there was made an experiment, enabling to estimate the avarage of time of answering (realizeing), definite types of questions- what means eficiency of each technologies.